2021
DOI: 10.3390/su13158360
|View full text |Cite
|
Sign up to set email alerts
|

Why Is Collaborative Apparel Consumption Gaining Popularity? An Empirical Study of US Gen Z Consumers

Abstract: Apparel rental, also known as collaborative apparel consumption, has created an innovative and popular business model, providing consumers with the ability to focus on using their products instead of ownership. Recent surveys show that sustainability is driving demand and customer loyalty in the US. Among all generations, Gen Z consumers lead the way. To better understand the emerging popularity of apparel rental services among Gen Z consumers who are becoming a major driving force for retail growth and the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
85
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(92 citation statements)
references
References 72 publications
7
85
0
Order By: Relevance
“…Despite recent bumps in the road, apparel renting continues to increase in popularity and is likely to become more common in the future [15]. Previous research has indicated that rental apparel models are more sustainable than traditional consumption models [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite recent bumps in the road, apparel renting continues to increase in popularity and is likely to become more common in the future [15]. Previous research has indicated that rental apparel models are more sustainable than traditional consumption models [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent bumps in the road, apparel renting continues to increase in popularity and is likely to become more common in the future [15]. Previous research has indicated that rental apparel models are more sustainable than traditional consumption models [15][16][17]. The reasons for this greater sustainability include being able to extend the life of products through use intensification and item repair; designing more durable products that last longer to avoid creating unnecessary waste; the need to create fewer products that satisfy more people, which reduces resource, water, electricity, and material consumption; the opportunity to reduce water and energy usage while better preserving garments through more professional cleaning services and technologies utilized by clothing rental companies; and helping consumers reduce overconsumption [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the subjective norm tells us whether an individual believes the people close to them approve or disapprove of the behaviour. The reviewed B2C literature on renting clothes seems to report that the subjective norm is a significant predictor of intention (Becker-Leifhold, 2018;Lang & Joyner Armstrong, 2018;Lee & Huang, 2020;McCoy et al, 2021;Mishra et al, 2021;Pham et al, 2021;Tu & Hu, 2018). Furthermore, subjective norm appears to be a reliable predictor of intention in the literature on collaborative consumption in general (Ianole-Călin et al, 2020;Iran et al, 2019;Laurenti & Acuña, 2020;Lindblom & Lindblom, 2018;Roos & Hahn, 2019).…”
Section: Theory Of Planned Behaviourmentioning
confidence: 99%
“…From the B2C literature on renting clothes, attitude is most often the strongest predictor of renting intention (Becker-Leifhold, 2018;McCoy et al, 2021;Mishra et al, 2021;Tu & Hu, 2018). Ajzen (1985) describes attitude as an "individual's positive or negative evaluation of performing the behaviour" (p. 12).…”
Section: Theory Of Planned Behaviourmentioning
confidence: 99%